FEIBA: A Prohemostatic Agent - Cromwell, Caroline; Aledort, Louis M. (Seminars in Thrombosis and Hemostasis, 2012)
Factor eight inhibitor bypassing activity (FEIBA), Anti-Inhibitor Coagulation Complex has been used for over 30 years in hemophiliac patients with inhibitors. The history of its use is reviewed here, including issues related to thrombosis, efficacy, and comparison to alternative bypassing agents. The need for surrogate assays to monitor effective hemostasis with the use of FEIBA remains.
Keywords: inhibitors; hemophilia; factor eight inhibitor bypassing activity; thrombosis